(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In a survey work done in year 2016-17 through personal interview of 20 families, in district Etawah, concluded that the average consumption of foods i.e. grains pulses, green vegetables, fruits, milk. Ghee and sugar in different age group i.e. 0.5 years, 11-18 years, 19-60 years and above 60 years was very low, which could not fulfill the minimum requirement of energy level (2400 calories in rural and 2100 calories in town level per headday). There were many food security related plans implemented by government in the district which performed better response to ensuring food security to the rural people. Government provided sufficient fund in every plan for supply of proper food in every year. But due to miss-management and unawareness, the funds and benefits of plans are unable to reach up to poor. So the condition of rural areas of Etawah was not satisfactory.